Improving the Accuracy of Independent Pronouns (Ḍamīr Munfaṣil) in Present Tense Verbs (Fi'l Muḍāri') Using Group Investigation (GI) Strategy in Arabic Writing Class - Siti Rifatul Milah; Sumiati Sumiati; Subhan Subhan; Ubaidillah Ubaidillah (Kitaba, 2026)
This study aims to determine the effectiveness of the Group Investigation (GI) strategy in improving students' Arabic writing skills (mahārah al-kitābah), specifically the accuracy of using independent pronouns (ḍamīr munfaṣil) with present tense verbs (fi'l muḍāri') at MAN 2 Pandeglang. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart spiral model, conducted in two cycles. The subjects were 31 students of class X-1. Data were collected through observation, written tests, and documentation. Quantitative data were analyzed using mean scores and classical mastery percentages, while qualitative data were analyzed through descriptive narratives of the learning process. The results showed that the use of the GI strategy significantly improved students' writing skills. The average class score increased from 59.35 in the pre-cycle stage to 71.74 in the first cycle, and further to 78.58 in the second cycle. Classical learning mastery increased from 19.35% to 54.84%, and then reached 90.32% in the second cycle, exceeding the Minimum Mastery Criterion (75) and the research performance indicator (80%). Student learning activity also increased from 77.02% (good category) in the first cycle to 91.94% (very good category) in the second cycle. The improvement was attributed to the integration of cooperative learning principles (positive interdependence, face-to-face interaction, individual accountability) and refinements made in the second cycle (smaller groups of three students, increased teacher guidance, more complex writing tasks). This study concludes that the Group Investigation strategy is effective in improving the accuracy of ḍamīr munfaṣil with fi'l muḍāri' in Arabic writing skills, bridging the gap between theoretical mastery and practical application through active, collaborative, student-centered learning.